The university student as partner. Its mediating role in the transition towards a professional identity - Franch Aguiló, Aina; Monereo, Carles (Journal of University Teaching and Learning Practice, 2025)
This study presents a case analysis in a university course where a partnership approach methodology was implemented, aiming to explore the construction of a Partner Identity Position (I-pP) and its relationship to professional development. Perceived professional dimensions by students were examined, along with the aspects of the course that contributed to their I-pP construction. Pre- and post-questionnaires, along with semi-structured interviews, were utilized.Results indicated a relationship between I-pP construction and perceived professional development. Most students experienced an increase in I-pP construction and perceived greater professional development. I-pP dimensions encompassed self-reflection, adaptability, cooperation, and support for others, aligning with professional positions described in the literature. Students highlighted the Service-Learning methodology, decision-making, and weekly reflections as key elements for their active engagement and commitment, in addition to the creation of a trustworthy environment with specific moments emphasizing the need for active participation. Results also suggest that I-pP can function as a metaposition within the student's role repertoire.In conclusion, this study emphasizes the relationship between I-pP and perceived professional development, as well as the necessary conditions to foster I-pP in the university setting. Despite limitations, these findings provide valuable insights into promoting a partner identity in higher education.